Means for Developing Students’ Ethics and Morality Through Participation in Islamic Spiritual Activities at SMPN 19 Surabaya - Arina Dewi Masithoh (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study aims to explore the impact of participation in Islamic Religious Activities as a means of developing students' ethics and morals at SMPN 19. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and document analysis related to Islamic Religious Activities at the school. The findings show that students' participation in these activities has a positive impact on their psychosocial well-being, including an increased sense of social connectedness and better emotional regulation. Moreover, these activities serve as an effective medium for developing students' ethics and morals by enhancing their awareness of religious values, honesty, and social responsibility. The implications of this study provide a clearer perspective on the important role of Islamic Religious Activities in supporting character development among students at SMPN 19 Surabaya.